Finite strain in the Moroccan Anti-Atlas: strain partitioning major Variscan dextral transpressive domains - Dias, Rui (2020)
The major Moroccan Tata and Tan-Tan Variscan shear zones show a strong strain partitioning ranging from orthogonal flexure to dextral flexural in adjacent beds. In the Moroccan Variscan Anti-Atlas major dextral shear zones are associated to this collision, like the Tata and the Tan-Tan shear zones. The interpretation of this deformation is debatable but finite strain analysis in the Ordovician Quartzites using Fry method and help to constrain the models. Away of the shear zones orthogonal flexural folding predominates while the shear zones show a strong strain partitioning ranging from orthogonal flexure to dextral flexural in adjacent beds as emphasized by Skolithos. The coaxial deformation predominating in the Anti-Atlas is coupled with non-coaxial dextral deformation along the shear zones. Such geodynamics is compatible with the dextral oblique collision between Gondwana and Laurussia in the Upper Palaeozoic.